Contemporary Conflict & The Fifth Generation of Warfare - CASIS-Vancouver (The Journal of Intelligence, Conflict and Warfare, 2018)
On February 22, 2018, CASIS Vancouver held its first event that featured a presentation by Simon Fraser University Adjunct Professor Candyce Kelshall on “Contemporary Conflict, and the Fifth Generation of Warfare.” Following the presentation, a question period provided insights into how to classify and identify fifth generation warfare (5GW) as opposed to the previous four generations of warfare. The roundtable discussion period focused on a case study of the Islamic State of Iraq and the Levant (ISIL) and their persecution of the Yazidis in order to illustrate the distinctive nature and character of 5GW.